2001
DOI: 10.1517/14656566.2.10.1671
|View full text |Cite
|
Sign up to set email alerts
|

Oseltamivir: a clinical and pharmacological perspective

Abstract: Oseltamivir is the ethyl ester prodrug of the antiviral molecule, oseltamivir carboxylate, a potent and selective inhibitor of influenza A and B neuraminidase (NA) (sialidase). It is highly bioavailable in capsule and suspension formulations and, after conversion to the active metabolite in the liver, distributes throughout the body, including the upper and lower respiratory tract. Oseltamivir carboxylate is 3% bound to human plasma proteins and eliminated through the kidneys by a first-order process as unchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(10 citation statements)
references
References 42 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…In vitro studies have demonstrated the potent antiviral activity of oseltamivir against all strains of influenza A tested, including the avian H5N1 virus recently implicated in human influenza cases in Hong Kong (11). In this study, the failure of treatment might have been attributable to various factors such as dosage, pharmacokinetics, or host metabolism, since no changes were seen in the neuraminidase.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have demonstrated the potent antiviral activity of oseltamivir against all strains of influenza A tested, including the avian H5N1 virus recently implicated in human influenza cases in Hong Kong (11). In this study, the failure of treatment might have been attributable to various factors such as dosage, pharmacokinetics, or host metabolism, since no changes were seen in the neuraminidase.…”
Section: Discussionmentioning
confidence: 99%
“… 555 However, charged moieties can also hinder the internalization pathway by diffusion through the lipid bilayer due to insufficient lipophilicity of the compound. 556 These contradicting effects, improved adherence and decreased diffusion through the membrane, illustrate the importance of a balanced design of drug-like molecules.…”
Section: Illustrative Examples Of Photoswitches In Aqueous Mediamentioning
confidence: 99%
“…The terminal plasma elimination half-life is 1.8 hours in healthy adults. 12 It is reported that survival is significantly increased by timely oseltamivir in serious cases. It is generally well tolerated except for few cases who get nausea, 13 vomiting and diarrhoea.…”
Section: Discussionmentioning
confidence: 99%